Pengaruh Penyuluhan kepada Keluarga dalam Pemberian Dukungan Ibu Nifas yang Mengalami Depresi Postpartum - Salsabila, Shafa; Ambarwati, Dewi; Pangesti, Wilis Dwi (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
Postpartum depression makes women who experience it less able to care for themselves, their families and their babies, while at the same time it can have a negative impact on quality of life. Family support is one of the influences on the mother's recovery. This study aims to determine the effect of counseling to families in providing support for postpartum mothers who experience psychological disorders in the postpartum depression stage. This research is a literature review using two databases: PubMed and Google Scholar. The keywords used are “assistance to the family of postpartum mothers in providing support for postpartum mothers” OR “assistance to the families of postpartum mothers in providing postpartum mother support” AND “Psychological disorders in the stage of postpartum OR depression”. After being selected with inclusion and exclusion criteria, a critical appraisal was carried out, 25 literatures were obtained consisting of 3 cross-sectional studies, 3 meta-analyses, 3 cohorts, 16 randomized controlled trials, 2 quasi-experimental studies, and 1 qualitative study. This study found 31 literatures that examined postpartum depression: risk factors, history of childbirth, early detection, signs and symptoms, prevention, treatment using herbal ingredients or the latest technology. To conclude, the effect of providing family support to postpartum mothers must be seen from the symptoms and risk factors for mothers experiencing postpartum depression.